School Curriculum and Parents’ Support on Kindergarten Students’ Caring Attitude - Dewi Natalia Puspitasari; Dini Mardila; Kartika Kirana (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2018)
Being care is an important attitude that children learn. Nowadays, itbecomes more important when children grow in the environment with workingparents, gadgets, television, and individual society. Therefore, ExperimentalMangunan Kindergarten has four values, and one of the values is ‘being care’. Thisresearch was held to find how school curriculum and parents support students’ caringattitude. This is a qualitative research with grounded theory method, which is held inExperimental Mangunan Kindergarten in Yogyakarta. There are two students’ casesin this research. The respondents of the interview were taken purposively. They werethe school principal, two teachers, and the students’ parents. Data collections wereheld by observation, interview, and reading teachers’ journals. The result was thatthe two students who have not yet caring to others when first entered MangunanSchool, were grow to have caring attitude after eight months. These findings showthat school curriculum, teachers’ and parents’ relation toward kindergarten studentsare important part to grow students’ caring attitude.